Domestic violence: the battered women syndrome as a defence of murder in Malaysia as compared to The United Kingdom / Izazi Muhammedin and Nadiatul Syima Ismail - Muhammedin, Izazi; Ismail, Nadiatul Syima (2007)
The last two semesters had been dedicated to conduct a research based on the issue of domestic violence which leads to murder between the husband and wife in Malaysia. The research was done with the objective to find out the sufficiency of the relevant law regarding the offence of murder in Malaysia and we also want to suggest a new law shall be created in order to protect the battered women who is suffering from battered women syndrome. The relevancy of the existing Domestic Violence Act 1994 will be taken into consideration also. We also had done research on the issue of battered women syndrome in the other countries like the United States of America (USA), Canada, New Zealand, Scotland, Australia and United Kingdom (UK). We also had make comparisons with the existing law in UK in regards to the battered women syndrome. The International cases which had been decided and highlighted by the courts are our main sources of information since in Malaysia, there are limited sources of the reading material on the topic of battered women syndrome. Our research is also based on the literatures written by authors in this area and also materials we find via online. We also had conducted interview sessions with experts that deals with the issues of the domestic violence and battered women syndrome. The outcomes of the interviews are as we expected. We benefit a lot from the interviews since most of the recommendations are relevant for the purpose of the research.